(untitled) (Aporia, 2020)
In this short paper I would like to propose the following: human judgments of morality are not, and can not be objective given unavoidable aspects of human neural anatomy. They can be influenced by brain damage, your genetics, or even switched up and down in intensity at will using methods like Transcranial Magnetic Stimulation (TMS), which I shall later discuss. Therefore any sense of an ability to make objective morality judgments is an illusion